2015
DOI: 10.1089/ars.2014.6122
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Endoplasmic Reticulum Stress in Chronic Intermittent Hypoxia-Induced Deficits in Synaptic Plasticity and Long-Term Memory

Abstract: Aims: This study examined the role of endoplasmic reticulum (ER) stress in mediating chronic intermittent hypoxia (IH)-induced neurocognitive deficits. We designed experiments to demonstrate that ER stress is initiated in the hippocampus under chronic IH and determined its role in apoptotic cell death, impaired synaptic structure and plasticity, and memory deficits. Results: Two weeks of IH disrupted ER fine structure and upregulated ER stress markers, glucose-regulated protein 78, caspase-12, and C/EBP homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 75 publications
(86 reference statements)
7
80
0
Order By: Relevance
“…The supernatant was centrifuged again at 3500 g for 10 min at 4 °C to obtain the mitochondrial fractions (deposition). Activities of respiratory chain complex I were measured by NADH-ubiquinone oxidoreductase methods [25, 26]. Mitochondria samples (0.5 mg/ml, 20 μl) were added to 165 μl of reaction buffer (50 mM KCl, 10 mM Tris-HCI, 1 mM ethylenediaminetetraacetic acid [EDTA], 2 mM KCN, 5 μM CoQ1) and incubated for 5 min at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was centrifuged again at 3500 g for 10 min at 4 °C to obtain the mitochondrial fractions (deposition). Activities of respiratory chain complex I were measured by NADH-ubiquinone oxidoreductase methods [25, 26]. Mitochondria samples (0.5 mg/ml, 20 μl) were added to 165 μl of reaction buffer (50 mM KCl, 10 mM Tris-HCI, 1 mM ethylenediaminetetraacetic acid [EDTA], 2 mM KCN, 5 μM CoQ1) and incubated for 5 min at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…; Xu et al . ). Increased ER stress is also associated with the pathogenesis of AD (Salminen et al .…”
Section: Hypoxia Activates γ‐Secretasementioning
confidence: 97%
“…Both hypoxia and ischemia are potent inducers of endoplasmic reticulum (ER) stress in the brain (Xin et al 2014;Xu et al 2015). Increased ER stress is also associated with the pathogenesis of AD (Salminen et al 2009); this might be a consequence of the presence of mild local hypoxia and disturbances in the maintenance of proteostasis.…”
Section: Er Stressmentioning
confidence: 99%
“…These symptoms were associated with pulmonary fibrosis and endothelial apoptosis [4][5][6]. According to previous studies, endoplasmic reticulum (ER) stress activation had been found in IH model and plays a critical role in apoptosis [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…The protocol was well-accepted and utilized by other researchers to generate a sleep apnea model in rodent [8,[23][24][25]. Ordinary cages were placed in computercontrolled ventilation chambers (Oxycycler model A48XOV, Redfield, USA) to achieve IH exposures in the animals.…”
Section: Model Of Chronic Intermittent Hypoxia and Tudca Treatmentmentioning
confidence: 99%